Titanium dioxide for printing ink as well as preparation method and application of titanium dioxide
By combining the titanium dioxide precursor with a ruthenium salt and a silane coupling agent and covering it with a polymethyl methacrylate-layer silicate mineral, the problem of titanium dioxide in the prior art is solved, and a high-performance printing ink titanium dioxide is achieved.
Patent Information
- Application Number
- CN202411353369.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The prior art is difficult to take into account the dispersion, hiding power and other performance indicators of titanium dioxide in the field of internal printing inks.
By immersing the titanium dioxide precursor in a ruthenium salt solution, annealing, combined with a silane coupling agent and a polymethyl methacrylate-layer silicate mineral, a titanium dioxide-ruthenium composition coated with a polymethyl methacrylate-layer silicate mineral is formed.
It realizes high dispersion, stability, hiding strength, gloss and wear resistance of titanium dioxide, and is suitable for the preparation of printing inks.
Smart Images

Figure BDA0005062916260000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified titanium dioxide, and in particular to titanium dioxide for printing ink and a preparation method and application thereof. Background Art
[0002] Ink is the fourth largest application field of titanium dioxide after coatings, plastics and papermaking. As the core raw material of ink, titanium dioxide not only provides basic hiding power and color-reducing power, but also affects the hiding power, printing properties, color fastness, etc. of ink. Titanium dioxide prepared by different processes has different characteristics in ink applications, and the performance varies greatly.
[0003] There are two main types of titanium dioxide used in inks. One is titanium dioxide for surface printing inks, which requires titanium dioxide to provide good dispersibility and glossiness. The other is titanium dioxide for back printing inks, which requires titanium dioxide to provide good dispersibility and hiding power. Due to the different production processes of various manufacturers, the final performance of titanium dioxide products currently on the market varies greatly. By adopting different grinding and dispersing and inorganic coating processes, titanium dioxide can obtain different dispersibility and ink hiding power. At present, in the field of back printing inks, the dispersibility of titanium dioxide and the hiding power of ink cannot be taken into account. Most titanium dioxide can meet the requirements for dispersibility, but due to problems such as excessive grinding, the hiding power will deteriorate. A small part of titanium dioxide can provide relatively good hiding power, but the indicators such as dispersibility and oil absorption are not good. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a titanium dioxide for printing ink and its preparation method and application, which can take into account the performance of dispersibility, stability, hiding power, glossiness and wear resistance at the same time and is suitable for preparing printing ink.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing titanium dioxide for printing ink, comprising the following steps:
[0007] S1: immersing a titanium dioxide precursor in a ruthenium salt solution, taking out the mixture, centrifugally drying it, and then annealing it to obtain a titanium dioxide-ruthenium composite;
[0008] S2: surface-modifying the titanium dioxide-ruthenium composition with a silane coupling agent to obtain a modified titanium dioxide-ruthenium composition;
[0009] S3: subjecting the silicate mineral dispersion to in-situ polymerization reaction in the presence of an initiator, a methyl methacrylate monomer, and a linker to obtain a polymethyl methacrylate-layered silicate mineral;
[0010] S4: adding the modified titanium dioxide-ruthenium composition to the dispersion of polymethyl methacrylate-layered silicate mineral and grinding to obtain a mixture, then making the mixture into a dispersion, centrifuging the solid, and drying to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, which is the titanium dioxide for printing ink.
[0011] The preparation method of titanium dioxide powder of the present invention comprises the following steps: firstly immersing a titanium dioxide precursor in a ruthenium salt solution, compounding ruthenium and titanium dioxide after annealing and calcining to obtain a titanium dioxide-ruthenium composition, then grafting and modifying the titanium dioxide-ruthenium composition with a silane coupling agent, and finally wet-grinding a polymethyl methacrylate-layered silicate mineral so that the polymethyl methacrylate-layered silicate mineral is coated on the surface of the modified titanium dioxide-ruthenium composition.
[0012] Ruthenium and its compounds have good chemical stability at room temperature and are not easy to react with oxygen or other chemicals in the air, so ruthenium is compounded with titanium dioxide, which helps to improve the chemical corrosion resistance and long-term stability of the ink.
[0013] Silane coupling agent can significantly improve the interfacial compatibility and adhesion of polymethyl methacrylate (PMMA), so that layered silicate minerals and ruthenium salts can better adhere to the surface of titanium dioxide. Because flat particles are arranged more closely in the coating, they have better hiding power and higher gloss than spherical particles, so the titanium dioxide has high hiding power and high gloss. Because polymethyl methacrylate-layered silicate minerals are on the surface, due to the low surface energy and non-polar properties of PMMA, other substances are not easy to adhere to its surface, and after curing, the ink coating will have anti-adhesion properties. PMMA has high chemical stability and can improve the weather resistance and chemical resistance of ink, especially under UV irradiation, PMMA has good stability. PMMA has a high hardness, so it can also improve the wear resistance of ink and reduce the wear of the printed surface.
[0014] Preferably, in the step S1, the immersion time is 10 to 18 hours; the annealing temperature is 500 to 600° C., and the time is 1 to 3 hours.
[0015] Preferably, the ruthenium salt is ruthenium trichloride.
[0016] Preferably, the titanium dioxide precursor is K2Ti4O9;
[0017] Preferably, the mass ratio of ruthenium salt to titanium dioxide precursor is 1:(18-20).
[0018] Preferably, in step S2, the modification method of the titanium dioxide-ruthenium composition comprises the following steps: adding a solution to the titanium dioxide-ruthenium composition to prepare a dispersion, then adding a silane coupling agent solution to the titanium dioxide-ruthenium composition dispersion to carry out a grafting modification reaction, taking out, centrifuging, and drying to obtain a titanium dioxide-ruthenium composition modified by a silane coupling agent; the temperature of the grafting modification reaction is 70 to 80°C, and the time is 2 to 4 hours.
[0019] Preferably, the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane (KH570), 3-aminopropyltriethoxysilane (KH550), and hexadecyltrimethoxysilane (HDTMS), and more preferably KH550.
[0020] After modification by the above-mentioned silane coupling agent, titanium dioxide can be more easily dispersed in organic media, reducing agglomeration, thereby improving its dispersibility in solvent-based inks. Silane coupling agents form a reinforced interface layer between titanium dioxide and the matrix material, which helps to transfer stress and improve the mechanical properties of the composite material, such as tensile strength, flexural strength and impact strength.
[0021] Preferably, the mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:(8-11).
[0022] Preferably, the mass concentration of the silane coupling agent solution is 1-2 wt %.
[0023] Preferably, in step S3, the silicate mineral dispersion is first mixed with the linker and the monomer, then heated, and then an initiator is added to carry out an in-situ polymerization reaction, and then taken out and filtered, and after washing and drying, polymethyl methacrylate-layered silicate mineral is obtained; wherein the temperature of the in-situ polymerization reaction is 55-65°C, and the time is 20-28h.
[0024] Preferably, the mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:(8-11).
[0025] Preferably, the initiator is potassium persulfate.
[0026] Preferably, the linker is acryloyloxyethyl trimethyl ammonium chloride. Acryloyloxyethyl trimethyl ammonium chloride (AETAC) is a cationic monomer used as a linker in the synthesis of water-soluble polymers.
[0027] Layered silicate minerals are a type of silicate minerals with a layered structure. The structural feature is that silicon-oxygen tetrahedrons are interconnected by sharing most of the corner vertices (usually 3 / 4 of the corner vertices) to form a two-dimensional infinitely extended silicon-oxygen tetrahedron layer. In the layers of these minerals, the oxygen on the corner vertices of the silicon-oxygen tetrahedrons that are not shared has a residual negative charge, which can be combined with metal cations to form silicates. Some silicon-oxygen tetrahedrons may also be replaced by aluminum-oxygen tetrahedrons to form additional negative charges, which further combine with metal cations. Therefore, the present invention utilizes the cationic properties of AETAC. In order to attach the polymer chain to the surface of the silicate, the cations of the silicate are exchanged with AETAC to form a stable copolymer. The monomer generates polymethyl methacrylate. At the same time, the polymer chain is stably attached to the surface of the silicate through the copolymer, that is, polymethyl methacrylate-layered silicate minerals are obtained. AETAC improves the solubility and stability of polymethyl methacrylate-layered silicate minerals.
[0028] Preferably, the silicate mineral includes at least one of montmorillonite, vermiculite, muscovite and kaolin, and more preferably montmorillonite.
[0029] Preferably, the mass ratio of the monomer to the silicate mineral is (1.1-1.3):1.
[0030] Preferably, the mass ratio of the connector to the silicate mineral is (0.8-1):1.
[0031] Preferably, in step S4, the modified titanium dioxide-ruthenium composition is first ground for 5 to 10 minutes, polymethyl methacrylate-layered silicate mineral is dissolved in water to form a dispersion, and the modified titanium dioxide-ruthenium composition is added to the polymethyl methacrylate-layered silicate mineral dispersion and ground for 20 to 30 minutes; after grinding, the mixture is added with water to form a dispersion, and the dispersion is centrifuged at a speed of 7000 to 10000 r / min for 5 to 10 minutes, and then washed to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, that is, titanium dioxide for printing ink; wherein the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is (10 to 20):1.
[0032] In a second aspect, the present invention provides a titanium dioxide for printing ink, which is prepared by the preparation method of the titanium dioxide for printing ink.
[0033] In a third aspect, the present invention provides an application of titanium dioxide for printing ink in the preparation of printing ink.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The preparation method of the modified titanium dioxide of the present invention comprises the following steps: firstly immersing a titanium dioxide precursor in a ruthenium salt solution, and then annealing and calcining and compounding ruthenium and titanium dioxide to obtain a titanium dioxide-ruthenium composition, and then grafting and modifying the titanium dioxide-ruthenium composition with a silane coupling agent, and finally wet grinding polymethyl methacrylate-layered silicate mineral so that it is coated on the surface of the modified titanium dioxide-ruthenium composition. The titanium dioxide obtained by the above method has high dispersibility, stability, anti-adhesion, low wear and other properties, and has high hiding and high gloss properties when thinly coated, and is suitable for ink printing. DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0037] The sources of the reagents and instruments used in the implementation scheme are as follows:
[0038] Potassium tetratitanate whiskers (K2Ti4O9): manufacturer is Shanghai Dianyang Industrial Co., Ltd.;
[0039] Ruthenium trichloride: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., the brand is R817350;
[0040] Silane coupling agent:
[0041] 3-Aminopropyltriethoxysilane (KH550), manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd., brand A107147;
[0042] γ-Methacryloxypropyltrimethoxysilane (KH570), manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd., brand number S111153;
[0043] Hexadecyltrimethoxysilane (HDTMS), manufactured by Shanghai MacLean Biochemical Technology Co., Ltd., brand number H811004.
[0044] Methyl methacrylate (MMA): The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., and the brand number is M109629.
[0045] Connecting agent:
[0046] Acryloyloxyethyltrimethylammonium chloride (AETAC), manufactured by Shanghai MacLean Biochemical Technology Co., Ltd., brand A871964;.
[0047] Sodium carboxymethyl cellulose (CMC), manufactured by Shanghai MacLean Biochemical Technology Co., Ltd., brand number S804627.
[0048] Layered silicate minerals:
[0049] Montmorillonite, manufactured by Shanghai MacLean Biochemical Technology Co., Ltd., brand number M813515;
[0050] Vermiculite: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number V885843;
[0051] Kaolin: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number 768524;
[0052] Potassium persulfate: The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., and the brand number is P299302.
[0053] Linseed oil alkyd resin: manufacturer is Shaoguan Derui Chemical Industry Co., Ltd., color ≤5, acid value ≤15mgKOH / g, viscosity 15000±5000MPa·s / 25℃, brand name JC116;
[0054] Sodium hexametaphosphate: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number S817848;
[0055] Cobalt acetate tetrahydrate: manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., brand number is C110805;
[0056] Polydimethylsiloxane: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., and the brand number is P822627.
[0057] Rheometer: manufacturer is Guangzhou Putong Experimental Analysis Instrument Co., Ltd., brand is POTOP, model is PTNI-55 / 03;
[0058] Gloss meter: purchased from Shenzhen Huaruichang Technology Co., Ltd., brand is KSJ, model is MG6-F1.
[0059] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0060] Example 1
[0061] A method for preparing titanium dioxide for printing ink comprises the following steps:
[0062] S1: The titanium dioxide precursor is immersed in a ruthenium salt solution for 16 hours, the mixture is taken out, centrifugally dried, and annealed at 550°C for 2 hours to obtain a titanium dioxide-ruthenium composite; the mass ratio of the ruthenium salt to the titanium dioxide precursor is 1:19. The titanium dioxide precursor is K2Ti4O9; the ruthenium salt is ruthenium trichloride.
[0063] S2 adds a solution to the titanium dioxide-ruthenium composition to prepare a dispersion, then adds a silane coupling agent solution to the titanium dioxide-ruthenium composition dispersion to carry out a grafting modification reaction, takes it out, centrifuges it, and dries it to obtain a titanium dioxide-ruthenium composition modified by a silane coupling agent; the temperature of the grafting modification reaction is 70 to 80°C, and the time is 2 to 4 hours. Wherein, the silane coupling agent is 3-aminopropyltriethoxysilane (KH550). The mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:10. The mass concentration of the silane coupling agent solution is 1.5wt%.
[0064] S3 first mixes the silicate mineral dispersion with the linker and methyl methacrylate monomer, then heats the mixture, adds an initiator, performs in-situ polymerization at 60°C for 24 hours, takes out the mixture, filters it, washes it, and dries it to obtain polymethyl methacrylate-layered silicate mineral; wherein the initiator is potassium persulfate. The linker is acryloyloxyethyl trimethyl ammonium chloride. The silicate mineral is montmorillonite. The mass ratio of the monomer to the silicate mineral is 1.2:1. The mass ratio of the linker to the silicate mineral is 0.9:1.
[0065] S4 first grinds the modified titanium dioxide-ruthenium composition for 6 minutes, dissolves polymethyl methacrylate-layered silicate mineral in water to prepare a dispersion, adds the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral dispersion and grinds for 25 minutes; after grinding, adds water to the mixture to prepare a dispersion, centrifuges the dispersion at a speed of 8000r / min for 8 minutes, and then washes to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, which is titanium dioxide for printing ink; wherein the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is 15:1.
[0066] Example 2
[0067] A method for preparing titanium dioxide for printing ink comprises the following steps:
[0068] S1: The titanium dioxide precursor is immersed in a ruthenium salt solution for 10 hours, the mixture is taken out, centrifugally dried, and annealed at 500°C for 3 hours to obtain a titanium dioxide-ruthenium composite; the mass ratio of the ruthenium salt to the titanium dioxide precursor is 1:18. The titanium dioxide precursor is K2Ti4O9; the ruthenium salt is ruthenium trichloride.
[0069] S2 adds a solution to the titanium dioxide-ruthenium composition to prepare a dispersion, then adds a silane coupling agent solution to the titanium dioxide-ruthenium composition dispersion to carry out a grafting modification reaction, takes it out, centrifuges it, and dries it to obtain a titanium dioxide-ruthenium composition modified by a silane coupling agent; the temperature of the grafting modification reaction is 70°C and the time is 4 hours. Wherein, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane (KH570). The mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:8. The mass concentration of the silane coupling agent solution is 1wt%.
[0070] S3 first mixes the silicate mineral dispersion with the linker and methyl methacrylate monomer, then heats it, adds the initiator, performs in-situ polymerization at 55°C for 28 hours, takes it out and filters it, washes and dries it, and obtains polymethyl methacrylate-layered silicate mineral; wherein the initiator is potassium persulfate. The linker is acryloyloxyethyl trimethyl ammonium chloride. The silicate mineral is vermiculite. The mass ratio of the monomer to the silicate mineral is 1.1:1. The mass ratio of the linker to the silicate mineral is 0.8:1.
[0071] S4: first grind the modified titanium dioxide-ruthenium composition for 5 minutes, dissolve the polymethyl methacrylate-layered silicate mineral in water to prepare a dispersion, add the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral dispersion and grind for 20 minutes; after grinding, add water to the mixture to prepare a dispersion, centrifuge the dispersion at a speed of 7000r / min for 10 minutes, and then wash to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, which is titanium dioxide for printing ink; wherein the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is 10:1.
[0072] Example 3
[0073] A method for preparing titanium dioxide for printing ink comprises the following steps:
[0074] S1: The titanium dioxide precursor is immersed in a ruthenium salt solution for 18 hours, the mixture is taken out, centrifugally dried, and annealed at 600°C for 1 hour to obtain a titanium dioxide-ruthenium composite; the mass ratio of the ruthenium salt to the titanium dioxide precursor is 1:20. The titanium dioxide precursor is K2Ti4O9; the ruthenium salt is ruthenium trichloride.
[0075] S2 adds a solution to the titanium dioxide-ruthenium composition to prepare a dispersion, then adds a silane coupling agent solution to the titanium dioxide-ruthenium composition dispersion to carry out a grafting modification reaction, takes it out, centrifuges it, and dries it to obtain a titanium dioxide-ruthenium composition modified by a silane coupling agent; the temperature of the grafting modification reaction is 80°C and the time is 2h. Wherein, the silane coupling agent is hexadecyltrimethoxysilane (HDTMS). The mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:11. The mass concentration of the silane coupling agent solution is 2wt%.
[0076] S3 first mixes the silicate mineral dispersion with the linker and the monomer, then heats the mixture, adds the initiator, performs in-situ polymerization at 65°C for 20 hours, takes out the mixture, filters it, washes it, and dries it to obtain polymethyl methacrylate-layered silicate mineral; wherein the initiator is potassium persulfate. The linker is acryloyloxyethyl trimethyl ammonium chloride. The silicate mineral is kaolin. The mass ratio of the monomer to the silicate mineral is 1.3:1. The mass ratio of the linker to the silicate mineral is 1:1.
[0077] S4: first grind the modified titanium dioxide-ruthenium composition for 10 minutes, dissolve the polymethyl methacrylate-layered silicate mineral in water to prepare a dispersion, add the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral dispersion and grind for 30 minutes; after grinding, add water to the mixture to prepare a dispersion, centrifuge the dispersion at a speed of 10000r / min for 5 minutes, and then wash to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, which is titanium dioxide for printing ink; wherein the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is 20:1.
[0078] Example 4
[0079] The difference between Example 4 and Example 1 is that the linking agent in Example 4 is sodium carboxymethyl cellulose (CMC).
[0080] Example 5
[0081] The difference between Example 5 and Example 1 is that the silane coupling agent in Example 5 is γ-methacryloxypropyltrimethoxysilane (KH570).
[0082] Example 6
[0083] The difference between Example 6 and Example 1 is that the silane coupling agent in Example 6 is hexadecyltrimethoxysilane (HDTMS).
[0084] Example 7
[0085] The difference between Example 7 and Example 1 is that in step S4 of Example 7, the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is 9:1.
[0086] Example 8
[0087] The difference between Example 8 and Example 1 is that in step S4 of Example 8, the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is 22:1.
[0088] Example 9
[0089] The difference between Example 9 and Example 1 is that the mass ratio of ruthenium trichloride to titanium dioxide precursor in Example 9 is 1:17.
[0090] Example 10
[0091] The difference between Example 10 and Example 1 is that the mass ratio of ruthenium trichloride to titanium dioxide precursor in Example 9 is 1:21.
[0092] Comparative Example 1
[0093] The difference between Comparative Example 1 and Example 1 is that the titanium dioxide-ruthenium composition of Comparative Example 1 is not modified by a silane coupling agent.
[0094] Comparative Example 2
[0095] The difference between Comparative Example 2 and Example 1 is that the montmorillonite in Comparative Example 2 is not modified by polymethyl methacrylate.
[0096] Comparative Example 3
[0097] The difference between Comparative Example 3 and Example 1 is that in step S3 of Comparative Example 3, no linking agent is added.
[0098] Comparative Example 4
[0099] The difference between Comparative Example 4 and Example 1 is that in step S4 of Comparative Example 4, polymethyl methacrylate is directly added without adding montmorillonite.
[0100] Comparative Example 5
[0101] The difference between Comparative Example 5 and Example 1 is that: in step S1 of Comparative Example 6, no ruthenium trichloride solution is added, that is, titanium dioxide is not compounded with ruthenium.
[0102] Comparative Example 6
[0103] The difference between Comparative Example 6 and Example 1 is that the montmorillonite in Comparative Example 6 is replaced by silicon dioxide.
[0104] Application Examples 1 to 10 and Comparative Application Examples 1 to 8
[0105] Application Examples 1 to 10 and Comparative Application Examples 1 to 6 are application examples of Examples 1 to 10 and Comparative Examples 1 to 6, respectively, that is, the modified titanium dioxide of Examples 1 to 10 and Comparative Examples 1 to 6 are used to make inks, respectively, while Comparative Application Example 7 is a blank control group that directly uses unmodified titanium dioxide.
[0106] The inks of application examples 1 to 10 and comparative application examples 1 to 7 include the following components in percentage: 30% titanium dioxide, 35% alkyd resin, 30% toluene, and 1% cobalt drier in each group, wherein the cobalt drier is cobalt acetate tetrahydrate.
[0107] The ink of comparative application example 8 includes the following components in percentage: 30% titanium dioxide, 35% alkyd resin, 24% toluene, 1% cobalt drying agent, 3% dispersant, 1% leveling agent and 2% microcrystalline wax in each group; wherein the dispersant is sodium hexametaphosphate, the cobalt drying agent is cobalt acetate tetrahydrate, and the leveling agent is polydimethylsiloxane.
[0108] The preparation method of each group of inks comprises the following steps:
[0109] Add titanium dioxide and half of the solvent to a dispersing device and stir at high speed until a uniform slurry is formed. Then add the binder and continue stirring to fully mix and disperse the resin and pigment. Add the remaining solvent and other additives. Grind further on a three-roll mill or a sand mill until the required fineness and uniformity are achieved. Filter to remove possible impurities or agglomerates to obtain the inks of Application Examples 1 to 10 and Comparative Application Examples 1 to 8, that is, 18 groups of samples are obtained respectively.
[0110] In actual production, the ink formula can be adjusted to adjust product performance.
[0111] Performance Testing
[0112] The ink samples of Application Examples 1 to 10 and Comparative Application Examples 1 to 8 were subjected to the following tests:
[0113] 1. Fineness test
[0114] According to the national standard GB / T13217.3-2022, take 0.5g of ink and use a scraper fineness meter to scrape it from top to bottom. The fineness is expressed in microns (μm). The smaller the fineness, the better the dispersibility.
[0115] 2. Rheological properties test
[0116] Put the tested ink into two iron boxes, each containing no less than 15g of ink, remove bubbles, seal with cellophane and mark, and then cover the iron box. Put the iron box into a 75-80℃ automatic constant temperature box and a -15~-20℃ freezer for 72 hours, take it out and store it at room temperature. The fluidity of the ink stored at room temperature for more than 3 hours is measured, and the fluidity is compared with the ink that has not been heated and frozen.
[0117] Characterize the fluidity of ink according to the national standard GB / T14624.3-2008. Take 1mL of ink, put it in the fluidity tester, cover it with a glass sheet, put a weight on it, read the value after 15 minutes, measure the sample with a ruler, and expand the diameter. The diameter indicates the fluidity.
[0118] 3. Gloss test
[0119] Take 0.5g of ink and drop it on the scraping paper. Place the scraper on the applied ink sample, make the scraper perpendicular to the scraping paper, scrape it from top to bottom into a thin layer, dry it, and measure it with a gloss meter.
[0120] 4. Friction resistance test
[0121] Using a six-color gravure printing machine, the ink of each group is printed on the surface of the tipping paper through the gravure roller, and the tipping paper sample is cut according to the required specification width. Cut a test sample of 50.0mm×230.0mm, fix it on the friction table, and use a friction tester to rub it back and forth 15 times to observe the color fading of the printed surface. The "Color Fastness Fading Sample Card" can be used for grade assessment. When assessing, the part with the greatest friction damage can be placed side by side with the part that has not been rubbed. When the color difference between the part with the most friction damage of the ink print and the part that has not been rubbed is equivalent to the difference of a certain level in the "Color Fastness Fading Sample Card", it is assessed at that level. Level 5 is the best and level 1 is the worst; if it is between two levels, it can be rated as an intermediate level, for example, written as 2-3, which means that it is better than level 2 and level 3 is worse.
[0122] Table 1 Performance data of samples of each group of inks
[0123]
[0124] It can be seen from Table 1 that the variable of each group of inks is only titanium dioxide, which means that the titanium dioxide in the ink samples of Application Examples 1 to 3 has good dispersibility, stability, glossiness and wear resistance.
[0125] Since no dispersant, leveling agent, stabilizer or other additives are added to the ink of comparative application example 7, the ink performance is poor and does not meet the national standard of ink fineness <20μm and fluidity within the range of 28-36mm. Dispersant and leveling agent are added to the ink of comparative application example 8, but its gloss, dispersibility, stability and wear resistance are significantly lower than those of the ink of application example 1, indicating that the addition of the modified titanium dioxide of the present invention can effectively improve the performance of the ink.
[0126] The linking agent in the titanium dioxide preparation process of Application Example 4 is sodium carboxymethyl cellulose (CMC). Because CMC has poor dispersibility, good hydrophilicity, and is easy to clump, it leads to poor adhesion of PMMA and montmorillonite, resulting in the dispersibility, glossiness, and mechanical properties of titanium dioxide being affected. Moreover, CMC also has thermal stability defects. Heating it for a long time at above 80°C may denature the colloid, resulting in a significant decrease in viscosity and performance, thus affecting the high-temperature stability of the ink. In contrast, no linking agent is added in Application Example 3, which makes it difficult for PMMA and montmorillonite to form a stable complex, thus significantly affecting the performance of the ink.
[0127] The silane coupling agents used in Application Examples 5 and 6 are KH570 and HDTMS respectively. The leveling, fineness and stability of the ink are lower than those in Application Example 1, because KH550 in Application Example 1 has more amino functional groups than the other two agents, which provides additional reactivity and a variety of chemical bonding methods, making it more tightly bonded to PMMA, thereby improving the performance of the ink.
[0128] The amount of modified titanium dioxide-ruthenium composition added to the ink of Application Example 7 is too small, while the amount of modified titanium dioxide-ruthenium composition added in Application Example 8 is too high, and its dispersibility and stability are both reduced, indicating that the preferred range is that the mass ratio of the modified titanium dioxide-ruthenium composition to polymethyl methacrylate-layered silicate mineral is (10-20): 1. Similarly, the mass ratio of ruthenium trichloride to titanium dioxide precursor in Application Examples 9 and 10 is not within 1: (18-20), resulting in a decrease in ink performance.
[0129] In the modified titanium dioxide of comparative application example 1, the titanium dioxide-ruthenium composition is not modified by a silane coupling agent, and the dispersibility, stability and wear resistance of the ink are greatly reduced. This is because the silane coupling agent can significantly improve the interfacial compatibility and adhesion of polymethyl methacrylate (PMMA), thereby enabling the layered silicate minerals and ruthenium salts to better adhere to the titanium dioxide surface.
[0130] In the modified titanium dioxide of comparative application example 2, the montmorillonite is not modified by polymethyl methacrylate, and its stability and wear resistance are significantly reduced. This is because PMMA has high chemical stability, which can improve the weather resistance and chemical resistance of ink, especially under UV irradiation, PMMA has good stability. PMMA has high hardness, so it can also improve the wear resistance of ink and reduce the wear of the printed surface.
[0131] The modified titanium dioxide in Example 4 is a comparative example in which montmorillonite is not added, and the glossiness of the ink is significantly reduced. This is because montmorillonite itself has a flat particle structure, so it has better hiding power and higher glossiness than spherical particles, thereby improving the high hiding power and glossiness of titanium dioxide. At the same time, the layered structure of montmorillonite can be used as a stabilizer to improve the storage stability of the ink and reduce pigment sedimentation and stratification.
[0132] In comparative application example 5, no ruthenium is added to the modified titanium dioxide, and its stability is significantly reduced. This is because ruthenium can provide the ink with good room temperature stability, low temperature stability and high temperature stability, and can also improve the wear resistance of the ink.
[0133] In the modified titanium dioxide of comparative application example 6, silicon dioxide replaces montmorillonite, and its dispersibility and stability are slightly reduced, but the gloss and wear resistance of the ink are significantly reduced, so montmorillonite can improve the gloss and wear resistance of the ink.
[0134] In summary, the titanium dioxide obtained by the above method has high dispersibility, stability, anti-adhesion, low abrasion and other properties, and a thin coating has high hiding and high gloss properties, which is suitable for ink printing.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing titanium dioxide for printing ink, characterized in that: The following steps are involved: S1: immersing a titanium dioxide precursor in a ruthenium salt solution, taking out the mixture, centrifugally drying it, and then annealing it to obtain a titanium dioxide-ruthenium composite; S2: surface-modifying the titanium dioxide-ruthenium composition with a silane coupling agent to obtain a modified titanium dioxide-ruthenium composition; S3: subjecting the silicate mineral dispersion to in-situ polymerization reaction in the presence of an initiator, a methyl methacrylate monomer, and a linker to obtain a polymethyl methacrylate-layered silicate mineral; S4: adding the modified titanium dioxide-ruthenium composition to the dispersion of polymethyl methacrylate-layered silicate mineral and grinding to obtain a mixture, then making the mixture into a dispersion, centrifuging the solid, and drying to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, which is the titanium dioxide for printing ink.
2. The method for preparing titanium dioxide for printing ink according to claim 1, characterized in that: In the step S1, the immersion time is 10 to 18 hours; the annealing temperature is 500 to 600° C., and the time is 1 to 3 hours.
3. The method for preparing titanium dioxide for printing ink according to claim 1 or 2, characterized in that: At least one of the following (I) to (III): (I) the ruthenium salt is ruthenium trichloride; (II) the titanium dioxide precursor is K2Ti4O9; (III) The mass ratio of ruthenium salt to titanium dioxide precursor is 1:(18-20).
4. The method for preparing titanium dioxide for printing ink according to claim 1, characterized in that: In step S2, the modification method of the titanium dioxide-ruthenium composition includes the following steps: adding a solution to the titanium dioxide-ruthenium composition to prepare a dispersion, then adding a silane coupling agent solution to the titanium dioxide-ruthenium composition dispersion to carry out a grafting modification reaction, taking out, centrifuging, and drying to obtain a titanium dioxide-ruthenium composition modified by a silane coupling agent; the temperature of the grafting modification reaction is 70 to 80°C, and the time is 2 to 4 hours.
5. The method for preparing titanium dioxide for printing ink according to claim 1 or 4, characterized in that: In step S2, at least one of the following (I) to (III) is selected: (I) the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and hexadecyltrimethoxysilane; (II) the mass ratio of the silane coupling agent to the titanium dioxide-ruthenium composition is 1:(8-11); (III) The mass concentration of the silane coupling agent solution is 1-2 wt %.
6. The method for preparing titanium dioxide for printing ink according to claim 1, characterized in that: In the step S3, the silicate mineral dispersion is first mixed with the linker and the monomer, then heated, and then an initiator is added to carry out an in-situ polymerization reaction, and then taken out and filtered, and after washing and drying, polymethyl methacrylate-layered silicate mineral is obtained; wherein the temperature of the in-situ polymerization reaction is 55-65° C., and the time is 20-28 hours.
7. The method for preparing titanium dioxide for printing ink according to claim 1 or 6, characterized in that: In step S3, at least one of the following (I) to (V) is performed: (I) the initiator is potassium persulfate; (II) the linking agent is acryloyloxyethyl trimethyl ammonium chloride; (III) the silicate mineral comprises at least one of montmorillonite, vermiculite, muscovite and kaolin; (IV) the mass ratio of the monomer to the silicate mineral is (1.1-1.3):1; (V) The mass ratio of the linker to the silicate mineral is (0.8-1):
1.
8. The method for preparing titanium dioxide for printing ink according to claim 1, characterized in that: In the step S4, the modified titanium dioxide-ruthenium composition is first ground for 5 to 10 minutes, polymethyl methacrylate-layered silicate mineral is dissolved in water to prepare a dispersion, and the modified titanium dioxide-ruthenium composition is added to the polymethyl methacrylate-layered silicate mineral dispersion and ground for 20 to 30 minutes; after grinding, the mixture is added with water to prepare a dispersion, and the dispersion is centrifuged at a speed of 7000 to 10000 r / min for 5 to 10 minutes, and then washed to obtain a titanium dioxide-ruthenium composition coated with polymethyl methacrylate-layered silicate mineral, that is, titanium dioxide for printing ink; wherein the mass ratio of the modified titanium dioxide-ruthenium composition to the polymethyl methacrylate-layered silicate mineral is (10 to 20):
1.
9. A titanium dioxide for printing ink, prepared by the method for preparing titanium dioxide for printing ink according to any one of claims 1 to 8.
10. Use of titanium dioxide for printing ink in preparing printing ink.
Citation Information
Patent Citations
Nanometer inorganic-organic coated mica powder and preparation method thereof
CN110408240A
Preparation method of noble metal and nonmetal loaded nano titanium dioxide, photocatalyst water-based paint and preparation method thereof
CN110975866A
Delustering agent with low photocatalytic activity as well as preparation method and application thereof
CN112457691A
Preparation method of titanium dioxide for high-gloss high-dispersion ink
CN115850999A
Aqueous-dispersion dye for preparing high-elastic covers
RU2286365C1